Effect of chloride and sulfate ions on deactivation of TiO2 anatase in photocatalytic treatment of methylene blue and methyl orange / Hamisu Umar Farouk - Hamisu Umar , Farouk (2019)
Dye wastewaters contain dissolved organic compounds that are hazardous and very difficult to treat with conventional wastewater treatment methods. Photocatalytic treatment, an advanced oxidation process (AOP), of wastewater treatment, generators of hydroxyl radicals (•OH), is capable of degrading most organic compounds. The most commonly used photocatalyst for this purpose is titanium dioxide (TiO2) and its modified forms due to its stability and lower cost. However, the practical use of TiO2 is limited due to possibility of deactivation. In textile wastewater, the presence of dye-enhancers such as sodium chloride (NaCl) and sodium sulfate (Na2SO4), releases Cl− and SO42– in the solution, reported to further deactivate TiO2, but the interaction of these ions with TiO2 surface is not comprehensively studied and reported. Therefore, in this work, the effect of Cl− and SO42− on photocatalytic degradation of methylene blue (MB), a cationic dye and methyl orange (MO), anionic dye as model contaminants was run with TiO2 anatase, the experiments were conducted at different conditions. Fresh TiO2 (TF) and deactivated samples were compared for changes in elemental composition and how they affect the cumulative percent degradation (CPD). The CPD was used to measure the number of times, TiO2 could be used repeatedly before deactivation over a 60h period divided into 10 hourly runs. A bulb with UV irradiation of wavelength 360-400 nm (UVA) was used. On the effect of SO42– in MO, highest CPD 431.9% at pH4 was recorded. Sulfur (S) and Nitrogen (N) were not detected in any of MO samples. MB has highest CPD 294.5% at pH10 with added SO42–. S and N species were detected due to their presence in MB structure and from added SO42– ions and did not induce further deactivation. On the effect of Cl–, it was not detected in any of the MB or MO samples, Cl– did not contribute to deactivation because of the high CPD values. There were changes in the composition of other elements, Oxygen (O), Sodium (Na), and Carbon (C). All deactivated samples show decrease in O, higher in MB than in MO samples. MO with higher amounts of O generally have high CPD. In some MO samples, on deconvolution of O, regeneration or increase in lattice oxygen (O2−) was seen but did not increase the CPD. Na detected in some samples in MB and MO, due to added salts and higher values of Na in MO samples were due to the combined presence of Na+ in the MO structure, presence of Na on deactivated samples did not affect the CPD. There was increase in carbon (C) in all deactivated samples, with more C species in MB samples than in MO. In conclusion, samples irradiated with UV yielded highest CPD values and the highest variety of new adsorbed elements in both MB and MO. The carbon species C=O, C-O and C-C were the predominant cause of deactivation, generated and adsorbed on the TiO2 surface. It is feasible that these species were captured at the region of bridging O being the most probable source of •OH radical generation. Photocatalyst activity with reduced deactivation could be sustained with sufficient UV irradiation by generation of •OH continuously. The pH did not have a significant effect on the rate of deactivation.